Gli proteins in development and disease - Hui, Chi-Chung; Angers, Stephane (Annual review of cell and developmental biology, 2011)
Gli zinc-finger proteins are transcription factors involved in the intracellular signal transduction controlled by the Hedgehog family of secreted molecules. They are frequently mutated in human congenital malformations, and their abnormal regulation leads to tumorigenesis. Genetic studies in several model systems indicate that their activity is tightly regulated by Hedgehog signaling through various posttranslational modifications, including phosphorylation, ubiquitin-mediated degradation, and proteolytic processing, as well as through nucleocytoplasmic shuttling. In vertebrate cells, primary cilia are required for the sensing of Hedgehog pathway activity and involved in the processing and activation of Gli proteins. Two evolutionarily conserved Hedgehog pathway components, Suppressor of fused and Kif7, are core intracellular regulators of mammalian Gli proteins. Recent studies revealed that Gli proteins are also regulated transcriptionally and posttranslationally through noncanonical mechanisms independent of Hedgehog signaling. In this review, we describe the regulation of Gli proteins during development and discuss possible mechanisms for their abnormal activation during tumorigenesis.